Talk is better: Deliberative Experiments to Microterritorial Conflict Resolution (2020)
The following analysis develops a wider research program that focuses on making a contribution to solve social conflicts through argumentation. Therefore, it presents a political sciences theory background that emphasises on applied rhetoric and deliberation in scenarios characterized by both high levels adversity and social capital. Based on this perspective of policy analysis and theory, it is possible to have a better glimpse at the complex network of social interactions laying under the process of constructions of the public sphere. Hence, this paper studies the possibilities of implementing micro-territorial deliberation instruments as conflict resolution tools for the city of Medellin (Colombia), thus, calling them deliberative experiments.